The Contribution of Knowledge Management in Improving the Quality of Educational Services (A Field Study in Tishreen University) (Journal of Hama University, 2020)
The researcher in this study is examining the range of knowledge Management contribution on the quality of educational services in Tishreen University. The study sample included (319) members of the academic staff at Tishreen University. The questionnaire was the main tool for collecting data. Some interviews were conducted to enquire about some issues. The data was analyzed using the statistical program (SPSS 20).The main purpose of this study was to highlight the impact of knowledge Management on improving the quality of educational services, highlighting the significance of the Explicit Knowledge and Tacit Knowledge in the university in order to improve the quality of the provided educational services.One of the main results of the study was that there is a positive relationship between relying on knowledge types and improving the quality of the provided educational services. Thus, the more relying on knowledge and paying attention to the requirements of its application, the more it will improve the quality of the provided educational services. This is clear in the field study that the types of knowledge contribute to a total interpretation difference (53.248%) of the total variance or change in improving the quality of educational services at Tishreen University. The results showed that (Tacit Knowledge) had the greatest impact on improving the quality of the provided educational services with effect (1,489), followed by (Explicit Knowledge) with effect (0.677).